Labor Human Rights in International Law - Canessa, Miguel (2009)
In recent years, there has been a revaluation of International Labor Law and, as a result, it has been strengthened with labor human rights. In this line, this study aims to address this issue from the horizon of international law. The author has divided the analysis in five large parts. In the first section a concept is proposed for this select group of basic labor rights, just as they are running the arguments that justify their legal recognition in the instruments international human rights The second section addresses the identification of labor rights with social rights, as a way to devalue their legal relevance. This is an analysis that refutes the questions that question the location of social rights within the list of human rights. In the third section the singularities of labor human rights are highlighted, which makes it difficult to subject them to the classic division between civil rights and social rights. The fourth section establishes the international obligations that arise from labor human rights towards the States. Also, a brief tour is made about international control procedures and the most important pronouncements for the protection of labor human rights. And it will be highlighted that in general the control procedures in the different human rights systems, the variety of specialized control bodies, and the protection of the list of human rights at work and the pronouncements or comments on them eliminate any doubt about the justiciable nature of the labor human rights. Finally, in the last section the jus cogens laboral is presented as a pillar of international labor law. And in this regard, the author suggests that instead of forming a "hard core" of labor human rights, it is more important for international law of work highlight the existence of a jus cogens laboral.